Emerald ash borer: Risk-based strategies to pest management - Davydenko, K.; Skrylnyk, Y.; Vorobei, E.; Baturkin, D.; Meshkova, V. (Forestry and Forest Melioration, 2024)
Introduction The emerald ash borer (EAB, Agrilus planipennis), a highly invasive beetle native to northeast Asia, poses a severe threat to ash trees (Fraxinus spp.) in forests, urban areas, and agricultural landscapes. Since its introduction to North America in the 1990s, EAB has caused significant ecological and economic damage. Its spread to Europe, including Russia and Ukraine, has intensified these challenges. This review examines EAB’s impact, identification, and management strategies to mitigate its spread and minimize damage. Materials and Methods This review is grounded in an extensive analysis of publications in scientific journals worldwide, with a primary focus on the identification and management strategies for the EAB, as well as our previously published scientific papers addressing EAB and ash dieback in Ukraine. Results Regulation and monitoring. EAB is classified as a quarantine pest in Ukraine and is subject to regulatory control under EU regulations, with controls on ash material movement. Localized eradication measures, such as the felling and burning of infested trees, are implemented alongside phytosanitary monitoring. However, the ongoing military conflict presents significant challenges to containment efforts in some regions. Spread and detection. EAB spreads both naturally (at a rate of up to 20 km per year) and through human activities, such as the transport of infested wood. First officially detected in Ukraine’s Luhansk region in 2019, EAB has since expanded into Kharkiv and Kyiv. Monitoring is coordinated by the State Service of Ukraine for Food Safety and Consumer Protection (SSUFSC) and its regional departments. These entities rely on visual inspections, pheromone traps, and sentinel trees for detection. Key visual symptoms of infestation include crown dieback, epicormic shoots, thinning crowns, and increased woodpecker activity. Surveys prioritize high-risk areas, such as shelterbelts, forest edges, declining ash stands, urban parks, and wood-processing sites. Pheromone traps and girdled trap trees are deployed to capture adult EAB, with adjustments made for local conditions. EAB-specific symptoms include D-shaped exit holes, serpentine larval galleries, and characteristic canopy decline. Detection tools include prism and multifunnel traps baited with specific attractants such as (3Z)-hexenol. Girdled trap trees, though cost-effective, are destructive and suited for delimitation efforts. Sentinel trees show promise for early detection. Differentiating EAB damage from ash dieback (Hymenoscyphus fraxineus) is essential for accurate diagnosis. Response framework. The SSUFSC oversees response efforts based on EAB contingency plans and EPPO standards. Upon confirmation of an infestation, quarantine zones are established, and infested trees are felled and destroyed. Regional SSUFSC departments coordinate with landowners to halt tree harvesting and restrict the movement of potentially infested materials. Post-confirmation strategies include containment through selective felling, insecticide applications, biological control, and public awareness campaigns. Eradication aims to remove all infested trees within a specific radius, though its success depends on early detection and limited spread. Eradication or Containment Strategies. Eradication focuses on removing all infested ash trees within a designated area, based on studies indicating limited dispersal distances of EAB larvae. However, eradication success depends on early detection and minimal spread. If complete eradication is not feasible, management efforts shift toward slowing the spread through selective felling, monitoring, and trap deployment. Challenges and Recommendations. The establishment of EAB in Ukraine highlights weaknesses in quarantine measures and the complexity of pest managment amid hostilities and climate change. Long-term strategies, such as integration of resistant ash genotypes and promoting tree species diversification, are essential to restore ecological balance and mitigate future risks. Conclusions EAB is a severe pest now established in three regions of Ukraine. This review outlines key steps for early detection, containment, and impact mitigation. While eradication has proven challenging globally, adaptive strategies, including resistant genotypes and forest diversification, offer hope for managing EAB’s ecological and economic impacts. 1 Fig., 24 Refs.